Elaine Steinbeck and E. L. Doctorow - :::::::::::::::
Elaine Steinbeck with E. L. Doctorow at the renaming of Bay Street Theatre's stage after Elaine. Doctorow read from John Steinbeck's letters to Elaine. Doctorow's classic Ragtime was adapted to the stage by Terrence McNally. The Bay Street Theatre is located in Sag Harbor, New York.